Women's career interruptions and the declining fertility rate in South Korea - Duksang Cho; Jungmin Han (Korea Development Institute (KDI), 2024)
In South Korea, more women are postponing or forgoing childbirth due to concerns about career interruption. Their conscious decision to refrain from motherhood is estimated to be responsible for about 40% of the decrease in the fertility rate. In the face of the world's lowest fertility rate, Korea needs to overhaul its policies to better support work-life balance, enabling parents to maintain their careers while raising children.
Keywords: 330